2018
DOI: 10.3389/fimmu.2018.02394
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Memory T Cells at Home in the Tissue: Mechanisms for Health and Disease

Abstract: During the last 10 years, a population of clonally expanded T cells that take up permanent residence in non-lymphoid tissues has been identified. The localization of these tissue resident memory (TRM) cells allows them to rapidly respond at the site of antigen exposure, making them an attractive therapeutic target for various immune interventions. Although most studies have focused on understanding the biology underlying CD8 TRMs, CD4 T cells actually far outnumber CD8 T cells in barrier tissues such as lung a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 103 publications
3
56
0
Order By: Relevance
“…Generally, the T-dependent process is able to imprint immune system with Ag features to establish the immune memory, which is marked by forming the long-lived memory T cells (including CD4+ and CD8+ MTCs) [38,43], possibly, derived from their effector counterparts [44], and long-lived memory B cells in LNs, spleen and peripheral tissues [45]. The generated immune memory is thought the most important consequence of vaccination as it enables the pathogen-experienced hosts to possess the ability of rapidly initiating responses to the encountered pathogens bearing identical Ags, thus engendering prompt immunity to remove invaders [32].…”
Section: Principles Underlying Vaccine Prophylaxis Of Infectious Disementioning
confidence: 99%
“…Generally, the T-dependent process is able to imprint immune system with Ag features to establish the immune memory, which is marked by forming the long-lived memory T cells (including CD4+ and CD8+ MTCs) [38,43], possibly, derived from their effector counterparts [44], and long-lived memory B cells in LNs, spleen and peripheral tissues [45]. The generated immune memory is thought the most important consequence of vaccination as it enables the pathogen-experienced hosts to possess the ability of rapidly initiating responses to the encountered pathogens bearing identical Ags, thus engendering prompt immunity to remove invaders [32].…”
Section: Principles Underlying Vaccine Prophylaxis Of Infectious Disementioning
confidence: 99%
“…Despite this, less is known about CD4 + T RM cells in infection settings, in comparison to their CD8 + T RM cell counterparts, or whether CD4 + T RM cells form effector T H cell subtypes, such as T H 1, T H 2, and T H 17, or even T FH cells. Recent evidence provided some insight, indicating that T H 1 [ 145 ] and T H 17-like [ 146 ] CD4 + T RM cells can mobilize in response to infection. However, the factors governing the development of these effector CD4 + T RM cell subtypes, especially in the context of memory responses to pathogen re-exposure, requires more definition.…”
Section: How T Cells Fight Bacteriamentioning
confidence: 99%
“…Several subsets of CD4 memory cells have been described, including central memory (TCM) and effector memory (TEM) cells which circulate through secondary lymphoid and non-lymphoid tissues 9 . More recently, tissue resident memory (TRM) cells that persist in barrier tissues such as lung and skin have been described 10 . Although CD4 T cells actually outnumber CD8 T cells in barrier tissues, the majority of studies have focused on the requirements for CD8 TRM cell differentiation.…”
Section: Mainmentioning
confidence: 99%
“…Accordingly, this approach tends to over-represent genes associated with type 1 helper T cells such as Klrg1, Itgae, Id2, and CXCR6, which may comprise a poorer definition of residency for other Th cell subsets.Consistent with this idea, the authors reported the presence of a stronger TRM phenotype in lymphoid Th1 memory cells compared to lymphoid TFH cells which they attributed to the relative ability of these cells to adapt to barrier tissues. On the other hand, it is well appreciated that TFH cells share many surface markers and molecular 4 dependencies with TRM cells, including high expression of PD1, P2X7R, CD69 and ICOS, and a requirement for S1PR1 and KLF2 downregulation to develop 10, 22, 23,24,25 . In support of this idea, TFH memory cells isolated from the spleen after LCMV infection were recently demonstrated to have a partially overlapping transcriptional signature with TRM cells, consistent with the non-circulating nature of both subsets 26 .…”
mentioning
confidence: 99%